Respuesta :
(x + 1)^2 = x^2 + 2x + 1
(x - 3)^2 = x^2 - 6x + 9
x^2 +2x + 1 = x^2 - 6x + 9 + 20 Cancel the x^2. add 9 and 20 together.
2x + 1 = -6x + 29 Add 6x to both sides.
2x + 6x + 1 = 29
8x + 1 = 29 Subtract 1 from both sides.
8x = 29 - 1
8x = 28 Divide by 8
x = 28/8
x = 3 4/8 = 3 1/2
(x - 3)^2 = x^2 - 6x + 9
x^2 +2x + 1 = x^2 - 6x + 9 + 20 Cancel the x^2. add 9 and 20 together.
2x + 1 = -6x + 29 Add 6x to both sides.
2x + 6x + 1 = 29
8x + 1 = 29 Subtract 1 from both sides.
8x = 29 - 1
8x = 28 Divide by 8
x = 28/8
x = 3 4/8 = 3 1/2